2020
DOI: 10.15446/abc.v25n3.79707
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL HISTORY OF THE BLACK IGUANA Ctenosaura similis (SQUAMATA: IGUANIDAE) IN ISLA CONTOY, QUINTANA ROO, MEXICO

Abstract: The genera Iguanaand Ctenosaurabelong to the Iguanidae family, and populations of most species of these genera have decreased due to anthropogenic effects. The natural history of most species of this family is poorly known, including Ctenosaura similis. Therefore, this study documents some ecological aspects of the species, such as its feeding habits, and habitat and microhabitat use in a population on Isla Contoy in Quintana Roo, Mexico. The data showed that even though C. similisis distributed throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…He also wrote that near houses, this iguana takes chicks of domestic hens and human feces (p. 91). Other authors have described this species as occasionally carnivorous, or indicate seasonal or ontogenetic changes in the species diet (Klein, 1977;García-Rosales et al, 2020). Fitch and Hackforth-Jones (1983) suggested that adult Black Iguana primarily eats leaves, flowers and fruits during the dry season, although their diet also includes small animals (Traveset, 1990).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…He also wrote that near houses, this iguana takes chicks of domestic hens and human feces (p. 91). Other authors have described this species as occasionally carnivorous, or indicate seasonal or ontogenetic changes in the species diet (Klein, 1977;García-Rosales et al, 2020). Fitch and Hackforth-Jones (1983) suggested that adult Black Iguana primarily eats leaves, flowers and fruits during the dry season, although their diet also includes small animals (Traveset, 1990).…”
mentioning
confidence: 99%
“…One interesting aspect of the food habits of this species is the occurrence of ontogenetic changes; juveniles prey mainly on insects (Montanucci, 1968;Lee, 2000) and reduces this intake to only 6% at the end of the first year of life, while adults feed mainly on plant material (Mora, 2010). This species can also eat carrion; there are two examples of it scavenging on toads (Pasachnik & Corneil, 2011;López & Mora, 2021), one fish, and at least three bird species (García-Rosales et al, 2020). Evidence of vertebrate predatory habits is less common, although few cases have been reported.…”
mentioning
confidence: 99%
See 3 more Smart Citations